Prevalence of foot diseases in cattle in two dairy farms - Sultana, Sharmin; Hossain, Md Akhtar; Hashim, Mirza Abul; Begum, Tahmina; Rahman, Bayzer; Rashid, Maksudur (Research in Agriculture Livestock and Fisheries, 2017)
The prevalence of claw affections was investigated in 602 cattle in two organized dairy farms during June 2010 to May 2011. Of these cattle 176 were from Bangladesh Agricultural University Dairy Farm (BAUDF) and 426 were from Central Cattle Breeding Station and Dairy Farm (CCBSDF). These animals were studied under 6 groups: calf, heifer, pregnant cow, lactating cow, dry cow and breeding bull. Out of 426 cattle in CCBSDF, 85 animals were affected with various claw affections, the prevalence being 19.95%. The prevalence in BAUDF was 22.72%. Claw affections causing lameness comprised sole ulcer (3.82%), heel erosion (2.49%), interdigital necrobacillosis (2.15%), sand crack (1.82%), hoof overgrowth (3.32%) and white line disease (2.32%). The prevalence of lameness in BAUDF was 13.06% and that in CCBSDF was 11.50%. Sole ulcer (3.82%) was predominantly associated with lameness in both farms while the lowest prevalence of lameness was encountered with interdigital dermatitis (1.39%). The lowest prevalence of lameness was observed in calves in both BAUDF (0.56%) and CCBSDF (0.93%). Pregnant cows were the most vulnerable to claw diseases and manifested lameness of varying degrees. Hind limbs were more frequently affected with claw affections than fore limbs. Animals of over 5 years were mostly affected with foot diseases. Breeding bulls showed 2.27% prevalence of lameness in BAUDF and 1.87% CCBSDF. Among various affections sole ulcer ranked the highest in both the farms. Sand crack and interdigital necrobacillosis registered the lowest prevalence in BAUDF and interdigital dermatitis was the lowest in CCBSDF. Sole ulcer ranked the highest among all claw affections. Pregnant cow were more vulnerable to lameness. Hind limbs were frequently affected with various lesions than the forelimbs. Res. Agric. Livest. Fish.4(3): 193-199, December 2017